Production potential and sustain ability of food-fodder alley cropping system under rainfed conditions - ARYA, R L; NIRANJAN, K P; SINGH, A; SINGH, J B (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during rainy season (kharij) of 1993-94 to 1995-96 at Jhansi to study theproductivity and sustainability of food-fodder alley cropping systems under dryland conditions ofBundelkhand region.Data revealed that significantly more grain, stover yield of sorghum, green fodder, dry-matter yield of fodder crops andsorghum grain equivalent yield were obtained in no tree association (control) compared with the farm boundary plantations with shisham (Dalbergia sissoo Roxb. ex DC) and alley species with subabul (Leucaena leucocephala (Lam.) de Wit). intercropping of sorghum (Sorghum bicolor L.) + pigeonpea (Cajanus cajan L. Millsp) gave significantly highest grain and stover yield of sorghum compared with the other systems. Sorghum + cowpea (Vigna unguiculata L.) intercropping system gave significantly highest green fodder and dry-matter yield compared with the sorghum + grass strips. Among the different manurial schedules, half inorganic fertilizer + half organic manure doses gave significantly highest grain and stover yield of sorghum, green fodder and dry-matter yield of fodder crops and sorghum grain equivalent yield over the other manurial schedules.